Central odontogenic fibroma: retrospective study of six cases with variable histopathologic features using 2022 WHO classification - Sopee Poomsawat; Sirada Choakdeewanitthumrong; Jira Kitisubkanchana; Theerachai Kosanwat (BMC, 2024)
Abstract Background Central odontogenic fibroma (COF) is a rare benign odontogenic tumor with a wide range of histopathologic features. We evaluated COF diagnosed in our institute with 16 years' experience using 2022 WHO classification. Methods Our archives were reviewed and cases diagnosed as COF were selected. Clinical, radiographic and microscopic features were tabulated and analyzed. Results Of 13,736 specimens, six cases (0.04%) of COF were discovered. Patients ranged in age from 14 to 44 years. There were two males and four females. Maxilla and mandible were affected equally. Five cases showed radiolucent appearance (4 unilocular, 1 multilocular) and one case showed a mixed radiolucent-radiopaque pattern. Histopathologically, three cases were conventional type (2 epithelium-rich, 1 epithelium-poor). Two cases were the hybrid COF with central giant cell granuloma (CGCG) and one of which was also associated with secondary aneurysmal bone cyst (ABC). The last case with a mixed radiolucent-radiopaque pattern was the ossifying subtype. Conclusion Our results demonstrated that COF is a rare odontogenic tumor and exhibits diverse radiographic and microscopic appearances. The triphasic tumor consisting of the COF, CGCG and ABC, is reported here for the first time, while the ossifying subtype is considered the tenth case reported in the English-language literature. Oral and maxillofacial pathologists and other healthcare personnel must be aware of this rare odontogenic tumor and its variants to achieve the definite diagnosis. Clinical trial number Not applicable.